Phenomenology of infrared finite gluon propagator and coupling constant - Natale, Adriano Antonio [UNESP] (2007)
We report on some recent solutions of the Dyson-Schwinger equations for the infrared behavior of the gluon propagator and coupling constant, discussing their differences and proposing that these different behaviors can be tested through hadronic phenomenology. We discuss which kind of phenomenological tests can be applied to the gluon propagator and coupling constant, how sensitive they are to the infrared region of momenta and what specific solution is preferred by the experimental data.